From Risk to Resilience: Uncovering Drug Recall Trends and Bolstering Safety Strategies - Kalidindi, Venkateswara Raju; Durga, Bandaru Mani Sai; Nori, Lakshmi Prasanthi (Indian Journal of Pharmaceutical Education and Research, 2024)
The process of officially calling something back to its original or initial location is termed as “recall.” Pharmaceutical recalls involve requesting to get back a product after it leaves the manufacturer to reach the distributor, retailer, or consumer. In place of the discovery of defect that affects the quality safety and efficacy of the product. Drug product recalls occur due to various reasons such as wrong or unapproved drugs, undeclared ingredients, contamination, incorrect information, and particulate issues. The probable risks or issues that arise due to a product recall or claims related to product liability and legal issues. A product recall should be perceived as an opportunity for the elimination of personal injury to the patient and damage to the reputation of the company products and rebuilding trust. Quality culture across the organization is a means of product recall prevention. In this comprehensive analysis, we delve into the drug recall statistics spanning the fiscal year 2018 to 2023 (up to July), focusing on the distinct challenges posed by recalls attributed to a lack of sterility assurance and those due to impurity profiles. Unveiling critical insights, the study highlights the impact of these issues on the pharmaceutical industry’s commitment to ensuring the safety and quality of drug products. This unique analysis presents a call to action for collaborative efforts between regulatory authorities, manufacturers, and healthcare professionals. Emphasizing the value of transparent communication and proactive measures, we explore avenues to mitigate recalls and reinforce public trust in pharmaceutical products. By drawing insights from past incidents, the industry can forge a path towards a safer, more reliable future, where drug recalls due to sterility and impurity issues become rare occurrences. Swift and thorough recalls are vital to ensure patient safety. The rising trend in recalls, caused by company discovery, customer complaints, or FDA observations, impacts sales, customer relations, and supply chains. Recalls involve planned actions, including depth of recall, public alerts, and effectiveness checks.
Keywords: Recalls; Sterility; Impurity; Public health; Observations